Nurse Clementine - James, Simon, 1961- (Somerville, Mass. : Candlewick Press, 2013)
After Clementine Brown receives a first-aid kit for her birthday, she begins to practice her skills on all of her family members except her reckless brother Tommy, who insists he doesn't need a nurse.
Keywords: Nurses -- Juvenile fiction; Nursing -- Juvenile fiction; Families -- Juvenile fiction; Picture books for children; Family life -- Juvenile fiction; Nurses -- Fiction; Nursing -- Fiction; Picture books